2017
DOI: 10.5539/ijef.v9n7p214
|View full text |Cite
|
Sign up to set email alerts
|

Does Institution Affect the Inflow of FDI? A Panel Data Analysis of Developed and Developing Countries

Abstract: The objective of this paper is to study the institutional impact on the net FDI inflow along with the other possible determinants of Foreign Direct Investment (FDI) in 40 countries comprising of developing and developed countries over the period of 1990-2010 by using panel econometric model. The dependent variable of our study is log of net FDI inflows measured at current US million dollars of different countries in different points in time and independent variables are log of GDP measured at current US dollar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 8 publications
(5 citation statements)
references
References 9 publications
1
4
0
Order By: Relevance
“…The findings of this study confirm the results of Sabir et al (2019), Mihaela et al (2018), Bailey (2018) Mallik and Chowdhury (2017), Siddica and Angkur (2017), Kurul and Yalta (2017) that control of corruption and adhering to the rule of law influence FDI positively, and a strict enforcement of property rights ensures safety and security of the foreign investments (Ayappan & Chin, 2018; Hossain, 2016; Cleeve (2008). The study also supports the claims of Sabir et al (2019), Kurul and Yalta (2017), Al Shubiri (2016), Mohamed and Sidiropoulos (2010), Cleeve (2008), Gani (2007) on the importance of fiscal freedom and government effectiveness and the claims of Sabir et al, 2019, Hossain (2016), Sánchez‐Martín et al (2014), Omanwa (2013) and Ines (2013) on the importance of trade freedom and openness in stimulating FDI.…”
Section: Discussionsupporting
confidence: 92%
See 1 more Smart Citation
“…The findings of this study confirm the results of Sabir et al (2019), Mihaela et al (2018), Bailey (2018) Mallik and Chowdhury (2017), Siddica and Angkur (2017), Kurul and Yalta (2017) that control of corruption and adhering to the rule of law influence FDI positively, and a strict enforcement of property rights ensures safety and security of the foreign investments (Ayappan & Chin, 2018; Hossain, 2016; Cleeve (2008). The study also supports the claims of Sabir et al (2019), Kurul and Yalta (2017), Al Shubiri (2016), Mohamed and Sidiropoulos (2010), Cleeve (2008), Gani (2007) on the importance of fiscal freedom and government effectiveness and the claims of Sabir et al, 2019, Hossain (2016), Sánchez‐Martín et al (2014), Omanwa (2013) and Ines (2013) on the importance of trade freedom and openness in stimulating FDI.…”
Section: Discussionsupporting
confidence: 92%
“…Aziz (2018) demonstrated that the institutional quality variables of economic freedom, ease of doing business and international country risk (ICRG) have a positive and significant impact on FDI inflows in Arab economies. Siddica and Angkur (2017) studied the inflow of FDI in 40 countries comprising developing and developed countries over the period of 1990-2010, using a composite institutional index. The study found that investment profile and law and order have a positive effect on FDI, while bureaucratic quality has a negative effect.…”
Section: Institutional Determinants Of Fdimentioning
confidence: 99%
“…Similarly, Mason and Vracheva (2017) concluded that in 50 developed and developing countries during 1996-2012, inflation had a negative influence on FDI inflows, and anti-inflation policies increased the recipient countries' attractiveness; however, according to the researchers, the attractiveness of antiinflation measures was mostly higher for developed countries. A negative impact of inflation on FDI inflows was also observed by Siddica and Angkur (2017) in 40 developed and developing economies from 1990 to 2010 and Gupta and Singh (2016). Therefore, inflation is used as an independent variable in order to consider the host economies' price unpredictability, macroeconomic stability and risk.…”
Section: Other Potential Determinant Factors Of Fdimentioning
confidence: 99%
“…Studies have shown that countries with strong institutional quality attract more foreign direct investment (FDI) than countries with weak institutional quality (Buchanan, Le & Rishi, 2012;Siddica & Angkur, 2017;Peres et al, 2018). North (1990) postulated that institutions are human-made limitations in form of political, economic and social interactions that reduce uncertainty and allow firms and individual to interact efficiently.…”
Section: Introductionmentioning
confidence: 99%